Twelve years of assessing the quality of preimplantation genetic testing for monogenic disorders - Deans, Zandra C; Biricik, Anil; De Rycke, Martine; Harton, Gary L; Hornak, Miroslav; Khawaja, Farrah; Moutou, Céline; Traeger-Synodinos, Jan; Renwick, Pamela (Prenatal diagnosis, 2023)
OBJECTIVE: Genomics Quality Assessment has provided external quality assessments (EQAs) for preimplantation genetic testing (PGT) for 12 years for eight monogenic diseases to identify sub-optimal PGT strategies, testing and reporting of results, which can be shared with the genomics community to aid optimised standards of PGT services for couples. METHOD: The EQAs were provided in two stages to mimic end-to-end protocols. Stage 1 involved DNA feasibility testing of a couple undergoing PGT and affected proband. Participants were required to report genotyping results and outline their embryo testing strategy. Lymphoblasts were distributed for mock embryo testing for stage 2. Submitted clinical reports and haplotyping results were assessed against peer-ratified criteria. Performance was monitored to identify poor performance. RESULTS: The most common testing methodology was short tandem repeat linkage analysis (59%); however, the adoption of single nucleotide polymorphism-based platforms was observed and a move from blastomere to trophectoderm testing. There was a variation in testing strategies, assigning marker informativity and understanding test limitations, some clinically unsafe. Critical errors were reported for genotyping and interpretation. CONCLUSION: EQA provides an overview of the standard of preimplantation genetic testing-M clinical testing and identifies areas of improvement for accurate detection of high-risk embryos.
Keywords: Aneuploidy; aneuploidie; genetické testování; Blastocyst; Pregnancy; lidé; preimplantační diagnóza; ženské pohlaví; Humans; Preimplantation Diagnosis; blastocysta; Female; těhotenství; Genetic Testing